Treatment for Mild Chronic Hypertension During Pregnancy. Issue 8 (August 2022) - Tita, Alan T.; Szychowski, Jeff M.; Boggess, Kim; Dugoff, Lorraine; Sibai, Baha; Lawrence, Kirsten; Hughes, Brenna L.; Bell, Joseph; Aagaard, Kjersti; Edwards, Rodney K.; Gibson, Kelly; Haas, David M.; et al.
Abstract : (Abstracted from N Engl J Med 2022;386:1781–1792) Chronic hypertension develops in 2% of pregnancies in the United States. As this condition disproportionately affects Black women and is associated with 3 to 5 times the risk of placental abruption, preeclampsia, preterm birth (PTB), small-for-gestational-age (SGA) birthweight, and perinatal death, optimizing treatment is critical to possibly preventing these associated complications.